VLCC‐Q: Very low computational complexity optical interconnect architecture with queueing for reducing delay and back pressure probability in data center networks. (20th April 2022) - Fayyaz, Mohsin; Shah, Yasir Ali; Fayyaz, Ahmed; Mujtaba, Ghulam
Summary: An architecture which promised very low computational complexity for optical interconnects in DCN was previously proposed, the very low computational complexity (VLCC) architecture. In this article, we present enhancement over VLCC architecture called very low computational complexity optical interconnect architecture with queueing (VLCC‐Q) architecture which represents M/D/64 output queue. Contention occurs at the destination if the source nodes which access the same destination node exceeds 64. The performance analysis is carried out through mathematical analysis, TCP simulation in NS2 and eye diagram of optical signal. The mathematical analysis gives theoretical bounds of optical switch, whereas TCP analysis gives practical situation results and eye diagram shows that optical signal is practically recoverable after the optical signal passes through various optical components of the optical interconnect. Results clearly show that VLCC‐Q outperforms VLCC architecture in terms of throughput increase, delay reduction and back pressure probability reduction.